Membaca Ulang 'Waiting for Godot' dengan Hermeneutika Paul Ricoeur - Pranowo, Yogie (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2015)
This paper presents an attempt of a philosophical exploration using Paul Ricoeur’s theory of text interpretation on Samuel Beckett’s Waiting for Godot. When viewed in a glance, Waiting for Godot does not appear much as a conceptual drama. It talks about so many things, ranging from things that sound trivial to things that smell theological. However, if one delves deeper through different interpretation, this drama is indeed intricate enough to provoke fresh insights. Its complexity is reinterpreted here insofar this drama is imagined within the genre of absurd drama. According to Ricoeur, one of the goals of interpretation is not only to understand the mind of the author behind the text, but the text itself with its circulating meanings around its interpretation, that is, within its interpretative world. The text gives rise to things for the understanding of the reader or interpreter. In the light of Ricoeur’s hermeneutics, this article attempts to reread some of the depths of Waiting for Godot. It is not so much of interpreting the intention of Samuel Beckett in writing the text as searching for different meanings in some parts of the dialogues in the text by way of engaging in its eventful discourse.